2018
DOI: 10.3847/1538-4357/aad04d
|View full text |Cite
|
Sign up to set email alerts
|

Radio Emission from the Cocoon of a GRB Jet: Implications for Relativistic Supernovae and Off-axis GRB Emission

Abstract: Relativistic supernovae constitute a sub-class of type Ic supernovae (SNe). Their non-thermal, radio emission differs notably from that of regular type Ic supernovae as they have a fast expansion speed (with velocities ∼ 0.6-0.8 c) which can not be explained by a "standard", spherical SN explosion but advocates for a quickly evolving, mildly relativistic ejecta associated with the SN. In this paper, we compute the synchrotron radiation emitted by the cocoon of a long gamma-ray burst jet (GRB). We show that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…SN 2009bb was discovered by the galaxy-targeted survey, the CHilean Automatic Supernova sEarch (CHASE; Pignata et al 2009a) on 21 March 2009 (Pignata et al 2009b) at the position of 10:31:33.8762, −39:57:30.022 (Bietenholz et al 2010) and was a broad-line type-Ic supernova (Stritzinger et al 2009). Radio and optical behaviour, and the relativistic ejecta velocity of SN 2009bb were very similar to those of low-z GRBs, especially GRB 980425 (SN1998bw; Soderberg et al 2010;Bietenholz et al 2010;Pignata et al 2011;De Colle et al 2018).…”
Section: Introductionmentioning
confidence: 60%
“…SN 2009bb was discovered by the galaxy-targeted survey, the CHilean Automatic Supernova sEarch (CHASE; Pignata et al 2009a) on 21 March 2009 (Pignata et al 2009b) at the position of 10:31:33.8762, −39:57:30.022 (Bietenholz et al 2010) and was a broad-line type-Ic supernova (Stritzinger et al 2009). Radio and optical behaviour, and the relativistic ejecta velocity of SN 2009bb were very similar to those of low-z GRBs, especially GRB 980425 (SN1998bw; Soderberg et al 2010;Bietenholz et al 2010;Pignata et al 2011;De Colle et al 2018).…”
Section: Introductionmentioning
confidence: 60%
“…lution of the slow-cooling synchrotron spectrum would suggest a delayed peak in the radio emission. This last scenario opens the possibility that the early radio emission is contaminated by another component, which could be the tail of the radio cocoon emission (De Colle et al 2018a). We also note that a good fit can be obtained with a less stratified environment and smaller observing angles (an R −2 medium is not the best choice for our models; a more detailed analysis will be presented in a future publication).…”
Section: Discussionmentioning
confidence: 91%
“…X-ray emission from the cocoon of a successful GRB is expected to peak a few hundred seconds after the explosion, and then to decay quickly (De Colle et al 2018a), similarly to what is seen in SN 2017iuk (Izzo et al 2019), thus not representing an important contribution in the emission on the observed timescale (≈days).…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, telling whether a misaligned relativistic jet is present is not easy, since all the radiation is relativistically beamed away from the line of sight. The slow but steady brightening was shown to be consistent with the presence of a jet, its energy contribution along the line of sight growing with the deceleration of the external shock (Xiao et al, 2017;De Colle et al, 2018;Finstad et al, 2018;Granot et al, 2018b;Lamb and Kobayashi, 2018;Lazzati et al, 2018;Fraija et al, 2019a;Fraija et al, 2019b;Beniamini et al, 2020b;Oganesyan et al, 2020). However, a radially stratified spherical outflow could reproduce the observations as well, albeit at the price of adding a never observed before component to the models (Li et al, 2018;Mooley et al, 2018c;Nakar and Piran, 2018;Salafia et al, 2018).…”
Section: The Afterglowmentioning
confidence: 76%